Long-term efficacy update of crizotinib in patients with advanced, inoperable inflammatory myofibroblastic tumour from EORTC trial 90101 CREATE. (October 2021) - Schöffski, Patrick; Kubickova, Michaela; Wozniak, Agnieszka; Blay, Jean-Yves; Strauss, Sandra J.; Stacchiotti, Silvia; Switaj, Tomasz; Bücklein, Veit; Leahy, Michael G.; Italiano, Antoine; Isambert, Nicolas; Debiec-Rychter, Maria; et al.
Abstract: Purpose: European Organisation for Research and Treatment of Cancer (EORTC) 90101 (CREATE) was a prospective, multicentric, non-randomised, open-label phase II basket trial to assess the efficacy and safety of crizotinib in patients with different types of cancers, including advanced inflammatory myofibroblastic tumour (IMT) with or without anaplastic lymphoma kinase ( ALK) rearrangements. Here, we report updated results with long-term follow-up. Patients/methods: After central reference pathology, eligible ALK- positive and ALK -negative patients with advanced/metastatic IMT deemed incurable with surgery, radiotherapy or systemic therapy received oral crizotinib 250 mg twice daily. The ALK status was assessed centrally using immunohistochemistry and fluorescence in situ hybridisation. The primary end-point was the proportion of patients who achieved an objective response (i.e. complete or partial response). If ≥6 ALK-positive patients achieved a confirmed response, the trial would be deemed successful. Results: At data cut-off on 28th January 2021, we performed the final analysis of this trial. Of the 20 eligible and treated patients (19 of whom were evaluable for efficacy), with a median follow-up of 50 months, five were still on crizotinib treatment (4/12 ALK-positive and 1/8 ALK-negative patients). The updated objective response rate (ORR) was 66.7% (95% confidence interval [CI] 34.9–90.1%) in ALK -positive patients and 14.3% (95% CI 0.0–57.9%) in ALK -negative patients. In the ALK -positive and ALK -negative patients, the median progression-free survival was 18.0 months (95% CI 4.0–NE) and 14.3 months (95% CI 1.2–31.1), respectively; 3-year overall survival rates were 83.3% (95% CI 48.2–95.6) and 34.3% (95% CI 4.8–68.5). Safety results were consistent with previously reported data. Conclusion: These updated results confirm previous findings that crizotinib is effective, with durable responses, in patients with locally advanced or metastatic ALK -positive IMT. With further follow-up after the original primary analysis, the ORR increased, as patients derived long-term benefit and some responses converted from stable disease to partial responses. Clinical trial number: EORTC 90101, NCT01524926. Highlights: No molecular agent has been approved for advanced, inoperable IMT. In this updated analysis, crizotinib achieved an ORR of 66.7% in ALK positive IMT. In ALK -positive IMT, the median PFS with crizotinib was 18.0 months (95% CI 4.0–NE). In ALK -positive IMT, the 3-year overall survival rate was 83.3% (95% CI 48.2–95.6). Crizotinib should be considered for approval in advanced ALK -positive IMT.